Rural Social Capital in Organic Farmer Institutions in Rice Organic Farming - Fadli Mulyadi; Septian Maulana Purnama; Jedda Ayu Inggrida (HABITAT, 2023)
Social capital is one of the seven fundamental capitals provided to groups or communities. Social capital is used to facilitate interpersonal interactions within a community or group. But nonetheless, only a small number of particular farmer groups, like the Sekar Putih Farming Group, have adopted organic farming methods to produce organic rice. One of the innovators and leaders in the production of organic rice is the Sekar Putih Farmer Group, who interpret the need for cohesiveness in interpersonal relationships. In theory, farmer groups are created because of the members' shared vision, mission, and goals as well as their shared work, which upholds the group's cohesiveness. 25 farmers were used as respondents with data collection using interview techniques, quantitative descriptive and scoring as data analysis methods. The results obtained are the formation of dynamics in farmer institutions, 37% of members have experienced conflicts but conflicts make the group more developed and conflicts can be controlled through equal empowerment. Social capital owned by the group has a high score, bonding social capital shows the togetherness of farmers in every cultivation process carried out and the distribution of information evenly to all group members. For bridging, it is shown by the number of training and empowerment programs that are often held and the Sekar Putih Group gets the opportunity to improve hard and soft skills in the cultivation process and information on market opportunities. In linking social capital, there is high trust in the acquisition of information related to fertilizers, pesticides and markets, this is inseparable from the communication that occurs among group members, both individually and in groups, relationships and interactions that are established can provide many positive sides.